Formation of microcapsules with fukoidan by external and internal jellification - Evgenija Vladimirovna Denisova; Viktoria Evgen'evna Suprunchuk; Anastasia Aleksandrovna Gorbacheva; Margarita Grigorjevna Shirinjan (Наука. Инновации. Технологии)
Investigated the relationship between structure and stability of the polysac-charide-based microcapsules kelp fucoidan, various crosslinking agents and stabilizers for modeling physiological conditions.